2023
DOI: 10.1007/s10815-023-02809-9
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial compaction is associated with the outcome of artificial frozen-thawed embryo transfer cycles: a retrospective cohort study

Abstract: Introduction The relationships between the outcome of frozen-thaw embryo transfer (FET) cycle and endometrial compaction were not quite consistent. Objective To analyze the relationship between the outcome of FET cycle and endometrial compaction. Materials and methods A total of 1420 women using FET were researched. The change in endometrial thickness on ET day and those on the day of progesterone (P) administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
1
0
0
Order By: Relevance
“…Additionally, no significant difference in LBR was found within PGT-A euploid ET cycles, fresh ET, or frozen (natural or HRT) ET cycles. In keeping with some studies, we also report significantly increased CPR ( Jarrah et al , 2021 ; Yaprak et al , 2021 ; Youngster et al , 2022 ; Ju et al , 2023 ) and OPR with EC ( Haas et al , 2019 ; Zilberberg et al , 2020 ; Kaye et al , 2021 ; Youngster et al , 2022 ). Of the 21 studies we included, only two reported on both OPR and LBR ( Huang et al , 2020 , 2021 ) and only four reported on both CPR (defined as a viable intrauterine pregnancy at less than 12 weeks’ gestation) and LBR ( Riestenberg et al , 2021 ; Yaprak et al , 2021 ; Gursu et al , 2022 ; Shah et al , 2022 ), thus, CPR/OPR and LBR results cannot be directly compared due to the large discrepancy in studies included in the meta-analyses and the amount of heterogeneity between the study protocols.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, no significant difference in LBR was found within PGT-A euploid ET cycles, fresh ET, or frozen (natural or HRT) ET cycles. In keeping with some studies, we also report significantly increased CPR ( Jarrah et al , 2021 ; Yaprak et al , 2021 ; Youngster et al , 2022 ; Ju et al , 2023 ) and OPR with EC ( Haas et al , 2019 ; Zilberberg et al , 2020 ; Kaye et al , 2021 ; Youngster et al , 2022 ). Of the 21 studies we included, only two reported on both OPR and LBR ( Huang et al , 2020 , 2021 ) and only four reported on both CPR (defined as a viable intrauterine pregnancy at less than 12 weeks’ gestation) and LBR ( Riestenberg et al , 2021 ; Yaprak et al , 2021 ; Gursu et al , 2022 ; Shah et al , 2022 ), thus, CPR/OPR and LBR results cannot be directly compared due to the large discrepancy in studies included in the meta-analyses and the amount of heterogeneity between the study protocols.…”
Section: Discussionsupporting
confidence: 92%
“…Ultrasound follow-up of natural menstrual cycles shows that the EMT reaches a peak just before ovulation and then either plateaus or thins, giving rise to EC ( Youngster et al , 2022 ). Some studies looking at EC have attempted to correlate it with serum oestradiol and progesterone levels, however, poor correlation exists ( Jarrah et al , 2021 ; Olgan et al , 2022 ; Youngster et al , 2022 ; Ju et al , 2023 ). Endometrial progesterone receptor deficiency, or resistance, may explain differences in EC among different patients/cycles as serum progesterone levels are not necessarily consistent with those within endometrial tissue ( Usadi et al , 2008 ; Lawrenz and Fatemi, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Youngster and his colleagues showed that the ratio of clinical and ongoing pregnancy was higher in the compacted group, which was consistent with the present study (12). Also, Ju et al showed that the percentage of clinical pregnancy was higher in the compacted group In this study, clinical pregnancy evaluation was done in patients undergoing frozen-thaw embryo transfer (FET) cycle (13). In another study, it was shown that live birth is directly related to endometrial compaction; so that, the incidence of live birth was higher in the compacted group.…”
Section: Discussionsupporting
confidence: 89%